Ambeng, Hazairin Zubair, Ngakan Putu Oka dan Adi Tonggiroh - Ambeng - Ambeng (Hasanuddin University, 2020)
Community structure analysis is one way to describe and assess the environmental quality of an ecosystem. One part of environmental biotic that make up mangrove water ecosystems is bivalves. The mangrove area in the Pangkajene river estuary has become one of the bivalve habitats, which has been widely used by the community. Research on the bivalve community structure of the mangrove area in the Pangkajene river estuary was conducted in April - June 2019, which aims to get an overview and assess the environmental conditions of the mangrove area in the Pangkajene river estuary based on the bivalve community structure. The research place was divided into three stations, each station was divided into two sampling areas, and in each sampling area six sampling points were placed. Sampling was carried out using a 50 x 50 cm plot method. Community structure limits calculated include density, diversity index, uniformity, dominance, and dispersion, as well as measurement of water parameters including pH, Organic C, and substrate texture. The results showed that the composition of bivalve community types consisted of 19 species included in 12 families. The dominant type is Saccostrea sp. with a density of 15.11 ind / m2 (Cr 50.77%). The species diversity index value ranges from 0.91 - 1.91 with an average of 1.50, which indicates the level of diversity of bivalves is relatively low. The Bivalvia community uniformity index includes the unstable criteria and the level of dominance index includes the stable community criteria, with a uniform distribution pattern.